Folk Devil Construction in The Symbolic Space of The City (A Study of Klitih in the City of Yogyakarta) - Sulhin, Iqrak; Harahap, Chisa Belinda (Jurnal Kriminologi Indonesia, 2026)
Yogyakarta is widely recognized as a city of culture and education, a symbolic identity institutionalized through historical narratives, political discourse, and cultural policy. The emergence of klitih—a term originally denoting aimless wandering but now associated with youth-perpetrated street violence—has challenged this image and generated intense public concern. While existing studies primarily explain klitih through causal factors such as peer influence, family supervision, and socio-economic conditions, this article shifts attention to the discursive construction of the phenomenon. Drawing on a constructionist approach and informed by cultural criminology and moral panic theory, the study analyses semi-structured interviews with government officials, law enforcement officers, journalists, and civil society actors, alongside representations in mass media and social media. The findings demonstrate that klitih has undergone a semantic transformation and is constructed as a “folk devil” that symbolically contaminates Yogyakarta’s urban identity. The strength of the city’s cultural branding amplifies moral panic and legitimises repressive governance responses. The article argues that in cities with strongly institutionalised symbolic identities, crime is framed not merely as deviance but as a paradox to urban meaning. By situating klitih within the symbolic politics of the city and Indonesia’s historical governance of crime, this study contributes to cultural criminology by demonstrating how moral panic operates in post-authoritarian urban contexts.